Potensi Tunikata rhopalaea sp. Sebagai Sumber Inokulum Jamur Simbion Penghasil Antimikroba - Erviana Tahir; Magdalena Litaay; Risco G Budji; Nur Haedar; Dody Priosambodo; Syahribulan Syahribulan (Hasanuddin University, 2016)
The research on the potency of tunicate Rhopalaea sp as a source of inoculum fungal symbionts that produce antimicrobial has been done. This research aimed to know the tunicate’s potency as a source of inoculum fungal symbionts and to characterize isolate symbiont fungal Rhopalaea sp. Isolation of fungi was performed using a PDA medium (Potato Dextrose Agar). Characterization of isolates fungal symbiont through macroscopic and microscopic observation, and testing its activity against pathogenic bacteria and fungi. The results showed there were three isolates(Asc 1, Asc 2 dan Asc 3) of fungal symbionts Rhopalaea sp. The results of macroscopic observation colony showed that Asc 1 had a flat surface such as cotton while Asc 2 and Asc 3 had a surface such as flour; Colours of isolates : Asc 1 (yellow), Asc 2 and Asc 3 (dark green). The result of microscopic observation reveals that Asc 1 had septa, Asc 2 and Asc 3 hadn’t septa; Asc 1 with blue brownish hyphae, while Asc 2 and Asc 3 hyaline (colorless); Asc 1 had asexual spores sporangiophores, while Asc 2 and Asc 3 had conidioshpore. Asc 1 isolate was suspected, belongs to the genus Penicillium and Asc 2 and Asc 3 isolates were suspected to be classified into the genus Aspergillus. All three isolates were able to inhibit the growth of Salmonella thypi bacteria and Candida albicans fungus.